Pelatihan Strategi Belajar Mandiri Berbasis Komunitas dan Kearifan Lokal di Kabupaten Lampung Tengah - Andre Lesmana; Yuli Supriani; Ahmad Rifai; Lilis Suryani; M. Agus Kurniawan; Nur Aisyah; Wahyu Lestari (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2026)
Independent learning ability is an essential competence in improving the quality of human resources in an era of rapid change. However, rural communities generally lack adequate independent learning strategies, while rich local wisdom has not been optimally utilized as a learning resource. This community service program aims to develop a training model for independent learning strategies based on local wisdom in five village communities in Central Lampung Regency. The implementation methods included interactive workshops, peer learning groups, individual mentoring, and communal reflection conducted over seven months involving 350 residents, 180 cultural and traditional leaders, and 120 village community administrators. The results showed a 119% increase in independent learning strategies, a 306% increase in the use of local wisdom as learning resources, and a 225% increase in community learning motivation.